Pemanfaatan Bahan Limbah Dari Kaleng Menjadi Sebuah Rak Pulpen - Halimatussa’diyah, Enni; Azri, Riza Nazila; Hakim, Muhammad Wildan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The popularity the idea of recycling recycled cans for use in metal crafts. of canned beverages. Pencils and other things are frequently placed directly into trash cans without being handled beforehand. However, it is possible to use recycled cans as the primary component in metal press engineering works. In addition to describing the production procedures and results of using used cans to build metal crafts with press techniques, this study aims to describe the can types that are best used as materials for such constructions. The procedures of observation, interviewing, and documenting were used to collect the data. The results showed that the best type of material for metal crafts manufactured using the press technique was soda cans (Tebs packaging, etc.). This kind of can is flexible, suited for compression techniques, and has a metal thickness of 0.3 mm (relatively thick). It can leave a mark by pressing it once or twice. The metal is very simple to mould, which saves time. The manufacturing process begins with cleaning used cans and cutting them into rectangular shapes. Next, drawings are created, then they are adhered, traced with used pencils or pens, shaped as desired, and finished. Keywords: utilization, used cans, press technique.